TRENDS IN CARBON DISCLOSURE RESEARCH: A BIBLIOMETRIC ANALYSIS - Sully Kemala Octisari; Bambang Agus Pramuka; Puji Lestari (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
Carbon disclosure is a company's voluntary disclosure related to the environment and greenhouse gas emissions. With increasing global warming and global public concern about the low-carbon economy, disclosing company information related to carbon emissions is one of the main focuses for investors. This article aims to look at research development trends in the field of carbon disclosure over the last 10 years using bibliometric analysis. The data in this study were sourced from the Scopus database and analyzed with the help of the Bibliomagika 1.8 application and the Biblioshiny of Bibliometrix R-package. A search in the Scopus database was carried out with the keyword "carbon disclosure" and produced 443 search results. The results of the bibliometric analysis show that research trends in the field of carbon disclosure have experienced steady growth over the last 10 years with authors from Australia and the United States dominating. Articles in the field of Carbon disclosure focus a lot on two main themes, diclosure related to carbon emissions and climate change as the causal factors for disclosing this information.